2016
DOI: 10.1097/md.0000000000004322
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative transfusion of leukocyte depleted blood products in gastric cancer patients negatively influences oncologic outcome

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…This is reflected by beneficial survival data for individual indications, which were also in good agreement with data in the literature: Jarnagin et al (intrahepatic and perihilar cholangiocarcinoma, 63 and 69% [ 17 ]; Zaydfudim et al (hepatocellular carcinoma, 6059 [ 18 ]; Schiergens et al and Margonis et al (CRLM 68% with transfusion and 82% without transfusion) [ 15 , 19 ]; esophageal cancer (40% with transfusion vs. 60% without transfusion) [ 20 ]; gastric cancer (82 vs. 60%) [ 16 ]; and pancreatic cancer (50 to 60% vs. 20%) [ 13 , 21 ]. Last not least, Mörner et al showed that anemia and transfusions were associated with adverse outcome [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is reflected by beneficial survival data for individual indications, which were also in good agreement with data in the literature: Jarnagin et al (intrahepatic and perihilar cholangiocarcinoma, 63 and 69% [ 17 ]; Zaydfudim et al (hepatocellular carcinoma, 6059 [ 18 ]; Schiergens et al and Margonis et al (CRLM 68% with transfusion and 82% without transfusion) [ 15 , 19 ]; esophageal cancer (40% with transfusion vs. 60% without transfusion) [ 20 ]; gastric cancer (82 vs. 60%) [ 16 ]; and pancreatic cancer (50 to 60% vs. 20%) [ 13 , 21 ]. Last not least, Mörner et al showed that anemia and transfusions were associated with adverse outcome [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…Sutton et al described an adverse outcome in pancreatic cancer (overall survival: 14 vs. 21 months) [ 13 ]. Other authors confirmed this for various indications: Martin et al (CRLM: odds ratio (OR) 4.18, 95% CI 2.18–8.02) and mortality (OR 14.5, 95% CI 3.08–67.8) [ 14 ], Schiergens et al (reduced recurrence-free survival (32 vs. 72 months in CRLM) [ 15 ], and Reim et al (gastric cancer: hazard ratio (HR) 1.31, 95% CI 1.01–1.69) [ 16 ]. However, these findings were based on dichotomization of data and not on the introduction of a structured program to reduce transfusions, which is the crucial difference to our work.…”
Section: Discussionmentioning
confidence: 99%
“…However, our multivariate analysis showed that perioperative blood transfusion was an independent factor for increased mortality and recurrence rate. Although blood transfusion is helpful for anaemic patients, emerging evidence has clarified that it is associated with poor clinical outcomes . In CRC patients who underwent curative resections, perioperative blood transfusions showed detrimental effects on recurrence .…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 While BTF is inevitable sometimes, transfusion-related immune modulation (TRIM) and systemic inflammation induced by a BTF not only leads to a higher incidence of postoperative complications, especially infections, but also poorer prognosis. 5 10 In addition, a growing body of evidence supports that postoperative complications adversely affect the long-term survivals of GC patients. 11 , 12 Given that both a BTF and postoperative infectious complications can cause a strong inflammatory response, and results in a pro-tumor environment, we hypothesized that a synergistic unfavorable effect may be observed for survival of GC patients who had both a BTF and infection, a question to the best of our knowledge that has not been previously addressed.…”
mentioning
confidence: 99%